Analysing the thermal performance of heat pipe using copper nanofluids - Baheta, A.T. (Penerbit Akademia Baru, 2018)
Heat pipes are heat transfer device that do not need external power; as a result, they are used in various thermal systems. Enhancing the performance of heat transfer device is a continues effort. Thus, this study investigates the effect of copper nanofluid on the thermal performance of cylindrical heat pipe (HP) that has screen mesh wick for heat transfer applications. The copper HP consists of 350 mm length and 12.7 mm outside diameter. To investigate its thermal performance mathematical model is developed. Demineralized water based 20 nm copper nanofluids with 0 to 4 particle concentrations were considered in the study. Simulation was done at 100 W heat input and results showed that when the particle concentration increases the evaporator wall temperature drops. At 4 particle concentration nanofluid the HP thermal resistance reduced by 17.5 compared to when the HP uses demineralized water. Furthermore, for a given particle concentration as the heat input increases the temperature change between the evaporator and the condenser increases. The outcome of the investigation can be input to the design of solar heat exchangers that use HPs filled with nanofluids. Â© 2018 Penerbit Akademia Baru.